Carotid Bifurcation With Tandem Stenosis—A Patient-Specific Case Study Combined in vivo Imaging, in vitro Histology and in silico Simulation - Wang, Jiaqiu; Paritala, Phani Kumari; Mendieta, Jessica Benitez; Gu, Yuantong; Raffel, Owen Christopher; McGahan, Tim; Lloyd, Thomas; Li, Zhiyong (Frontiers in Bioengineering and Biotechnology, 2019)
A patient-specific carotid bifurcation with tandem stenosis found at both internal carotid artery (ICA) and common carotid artery (CCA) was studied. The in vivo pre-carotid endarterectomy (CEA) multi-spectral magnetic coherence imaging (MRI) were performed and in vitro post-CEA carotid plaque tissue sample was collected. MR imaging data and tissue sample staining histology were used to recognise the plaque components. Further, the computational fluid dynamics (CFD) were performed on four MR-based reconstructed 3D carotid bifurcation models (the patient-specific geometry with tandem stenosis and three presumptive geometries by removing the stenosis part), the flow and stress behaviour affected by the tandem stenosis was analysed. From the results of MR segmentation and histology analysis, plaque lipid pool and calcification were found at both ICA and CCA. From the result of CFD simulation, the flow and stress behaviour suggested the tandem stenosis as a more ‘dangerous’ situation than a single-stenosis geometry. Besides, the CFD results deduced that the stenosis at the CCA location formed initially and lead to the subsequent formation of stenosis at ICA. This study suggests that when planning CEA, CFD simulation on the presumptive models could help clinicians to estimate the blood flow behaviour after surgery. Particular attention should be paid to the case of tandem stenosis, as the local hemodynamic environment is more complex and treatment of one stenosis may lead to a variation in the hemodynamic loading on the second plaque, which may result in either a higher risk of plaque rupture or restenosis.